(untitled) (Journal of Engineering, 2012)
An investigation was conducted for the study of extraction of metal ions using aqueous biphasic systems. The extraction of iron, zinc and copper from aqueous sulphate media at different kinds of extractants SCN− , Cl- and I- , different values of pH of the feed solution, phase ratio, concentration of metals, concentration of extractant, concentration of polymer, and concentration of salt was investigated. Atomic absorption spectrophotometer was used to measure the concentration of iron, zinc and copper in the aqueous phase throughout the experiments. The results of the extraction experiments showed the use of SCN− as extractant, pH=2.5, phase ratio=1.5, concentration of metals 1g/l, concentration of extractant 0.06 %, concentration of polymer =50 %, and concentration of salt=20% gave the highest value of percent removed. Also increase of extractant concentration increases the percent removed. The results clarified that increasing the metal ions concentration in the aqueous phase causes to decease the percent removed. The addition of an inorganic salt (sodium sulphate) up to (20%) increased the dehydration of polymer chains and then increases the percent removed.